PELATIHAN CALON PENELITI MUDA DI LINGKUNGAN MADRASAH TSANAWIYAH NEGERI 3 MAGETAN - Mutmainah Mutmainah; Arini Wildaniyati; Mintarti Indartini (JURNAL DAYA-MAS, 2022)
Abstract— The purpose of this society dedication activity is to prepare young prospective researchers to produce research that can be utilized by the wider community and poured in the form of scientific papers. This young prospective researcher who will produce new findings in solving problems and meeting the needs of society. This activity is in the form of mentoring and guidance to students of madrasah tsanawiyah seventh grade and eighth grade of excellent classes. Excellent classes are considered capable of being given higher knowledge. The activity was carried out for four months at Madrasah Tsanawiyah Negeri 3 Magetan. The result of this activity is that students get research ideas and can compile research reports in the form of scientific papers. From each of the classes that got the research idea about seven to eight children, and students' ability to draft proposals averaged 72.5 percent. This shows that madrasah students able to produce innovations in the future.